2020
DOI: 10.1111/hsc.13069
|View full text |Cite
|
Sign up to set email alerts
|

Administering the U.S. Family Violence Option: The role of stigma in waiver recommendations

Abstract: Domestic violence (DV) has a negative effect on the lives of women, contributing to significant physical and mental health issues, especially for women in poverty (Goodman, Smyth, Borges, & Singer, 2009). Perpetrators of DV can financially trap women in relationships using a variety of tactics including financial abuse (Postmus, Plummer, McMahon, Murshid, & Kim, 2012), which can negatively impact survivors' psychological well-being and quality of life (Adams & Beeble, 2019). Furthermore, DV is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Stigmatizing attitudes appeared in formal and informal supporters as well: Gutowski and Goodman [ 49 ] showed that most of the women in their study reported experiencing harsh behaviors and judgments from court professionals. In this regard, Nikolova and colleagues [ 56 ] confirmed these results with respect to advocates. Despite this, hand therapists have shown low levels of victim-blaming attitudes [ 60 ].…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Stigmatizing attitudes appeared in formal and informal supporters as well: Gutowski and Goodman [ 49 ] showed that most of the women in their study reported experiencing harsh behaviors and judgments from court professionals. In this regard, Nikolova and colleagues [ 56 ] confirmed these results with respect to advocates. Despite this, hand therapists have shown low levels of victim-blaming attitudes [ 60 ].…”
Section: Resultsmentioning
confidence: 57%
“…IPV survivors seem to be stigmatized when they do not have the following characteristics of ‘ideal victims’: (1) Weak, (2) they were doing something respectable when the violent episode occurred, (3) they cannot be held responsible for the circumstances in which the violence took place, (4) they faced bigger offenders, (5) they faced unknown perpetrators [ 56 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are currently no quantitative evaluation instruments for measuring public stigma, the methodologies used to date have been mainly qualitative. We found only a few correlational studies, such as the one mentioned above, in which an association was found between stigma and a low risk assessment by lawyers (Nikolova et al, 2021). Moreover, it is worth pointing out that the pioneering qualitative studies that identified the different manifestations of stigma (Crowe & Murray, 2015; C.…”
Section: Theory and Prior Research On Public Stigmatization Toward Ip...mentioning
confidence: 97%
“…This same review identified only four studies, in addition to the one mentioned above by Crowe and Murray (2015), that provided data on stigmatization by professionals working in the judicial system. Along with finding that professionals did not always believe victims or take them seriously (e.g., Merino et al, 2020; Ragusa, 2017), these studies also found that, regardless of the seriousness of the violence and its impact on the victim’s health, having only recently left the abusive relationship or continuing to live with the abuser had a negative influence on the risk assessment carried out by lawyers (Nikolova et al, 2021). The severity of these practices is that they jeopardize the safety, financial, and other basic needs of the victims (C.…”
Section: Theory and Prior Research On Public Stigmatization Toward Ip...mentioning
confidence: 99%